simplify the expressions. show your work. (5x^4-3x^3+6x)- (3x^3+11x^2-8x)

Question

Asked 3/25/2016 7:06:27 PM

Updated 3/25/2016 8:08:56 PM

1 Answer/Comment

Flagged by jeifunk [3/25/2016 8:08:04 PM]

s

Question

Asked 3/25/2016 7:06:27 PM

Updated 3/25/2016 8:08:56 PM

1 Answer/Comment

Flagged by jeifunk [3/25/2016 8:08:04 PM]

Rating

8

(5x^4-3x^3+6x)- (3x^3+11x^2-8x)

=(5x^4) + (-3x^3 + (-3x^3)) + (-11x^2) + (6x+8x)

=5x^4 - 6x^3 - 11x^2 + 14x

=(5x^4) + (-3x^3 + (-3x^3)) + (-11x^2) + (6x+8x)

=5x^4 - 6x^3 - 11x^2 + 14x

Added 3/25/2016 8:08:56 PM

This answer has been confirmed as correct and helpful.

What is the sum?
–7 + 5
A. –2
B. 12
C. –12
D. 2 **Weegy:** The sum: –7 + 5 = -2 (More)

Question

Expert Answered

Updated 3/23/2016 8:23:20 PM

0 Answers/Comments

What percent of 100 is 30?
A. 30%
B. 333%
C. 3.33%
D. 0.3% **Weegy:** 30% 100 is 30. 30/100 = x/100; 0.3 = x/100; x = 0.3 * 100; x = 30 (More)

Question

Updated 3/23/2016 6:47:35 PM

0 Answers/Comments

What are the solutions of the inequality? Check the solutions. 4x + 6 –3
B. x > –6
C. x **Weegy:** 4x + 6 < -6; 4x < -6 - 6; 4x < -12; x < -12/4; x < -3 (More)

Question

Updated 3/24/2016 7:29:23 AM

0 Answers/Comments

Factor the polynomial. 54c 3d 4 + 9c 4d 2
A.
9c 3d 2(d 2 + 6c)
B.
9c 3d 2(6d 2 + c)
C.
9c 4d 2(d 2 + 6)
D.
9c 4d 2(6d 2 + 1) **Weegy:** 54c^3d^4 + 9c^4d^2 = 9c^3d^2(6d^2+c) (More)

Question

Updated 3/23/2016 10:10:49 PM

0 Answers/Comments

What are the solutions of the equation?
c2 - 10c = 0
A.
1,
B.
0, –10
C.
0,
D.
0, 10 **Weegy:** The solutions of the equation c^2 - 10c=0 is c = 0 , c = 10 . c^2 - 10c = 0 c(c - 10) = 0 c = 0, c = 10 (More)

Question

Updated 3/23/2016 10:08:10 PM

0 Answers/Comments

32,519,548

questions answered

There are no comments.